Seleksi In Vitro Tanaman Lada untuk Ketahanan terhadap Penyakit Busuk Pangkal Batang - Ali Husni; Mia Kosmiatin (Jurnal AgroBiogen, 2005)
Root rot caused by Phytopthora capsici is one of the most important diseases of pepper, it can decrease yield up to 52%. Planting resistant plants is an efficient way to control the disease. In vitro selection is a method that can be utilized for selection of resistant plants. The objective of the study was to obtain pepper plants resistant to root rot disease through in vitro selection. The study consisted of four experiments, i.e., (1) induction of embryogenic calli, (2) production of filtrate of P. capsici, (3) in vitro selection and shoots regeneration, and (4) root induction. The results showed that leaf tissue was the best explants for production of embryogenic calli in a medium of Gamborg (macro nutrient) + MS (micro nutrients and vitamins) with 2.4-D 0.1 or 0.5 mg/l. The best filtrate of P. capsici culture used for the selection was that from the 5 day-old inoculum in the V8 medium. In general, addition of P. capsici culture filtrate into the regeneration media influenced the percentage of live calli. The addition of 50% and 75% of P. capsici filtrate was enabling to screening for adaptive calli based on brownish-yellow or yellowish-brown color. These calli produced 32 shoots in the regeneration media without the P. capsici filtrate. Root induction was successfully performed in the MS medium with 0.01 mg/l of NAA.